Hidden Costs of Control in Social Groups - Simon Wiederhold; Gerhard Riener (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper investigates the role of social identity in reactions to control. We propose a simple principal-agent model with control that incorporates the existence of social groups. Our laboratory experiment shows that, in contrast to no-group agents, agents in social groups (i) perform better; (ii) expect less control; (iii) do not reciprocate when facing less control than expected; (iv) decrease their performance substantially when actual control exceeds their expectation. Hidden costs of control thus appear to be more substantial in social groups.
Keywords: C92; M54; D03; 330